HUBUNGAN PENGETAHUAN GIZI DAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI KOTA KUPANG - Maria Goreti Pantaleon; Maria Helena Dua Nita; Meirina Sulastri Loaloka; Christine Rosanti Nenotek (Kupang Journal of Food and Nutrition Research, 2021)
Iron deficiency anemia is anemia that occurs due to iron deficiency which disrupted the formation of red blood cells and other functionalities. Nutritional anemia is very common in Indonesia and can occur in all group of ages, where the hemoglobin levels in the blood is lower than its standard (Adriani, M., et al, 2012). The results of the Basic Health Research (Riskesdas) of 2018 found that anemia cases in Adolescent Girls increased. In 2013, there were approximately 37.1 percent of adolescent girls suffered from anemia. This figure rose to 48.9 percent in 2018. Anemia was mostly suffered by female adolescent in two age groups, 15 to 24 year old-girls and 25 to 34 year-old girls (voice.com article, 2018). The purpose of this study is to analyze the relationship among nutritional knowledge, nutritional status and incidence of anemia in adolescent girls in Kupang. The sample in this study were 50 adolescent girls with or without anemia. The research was carried out from May to July 2021 at the Nutrition Study Program of Health Polytechnic of Kupang of Ministry of Health. The data were analyzed by using univariate and bivariate (Chi-Square) analysis. The results of the analysis showed that there was no relationship between nutritional knowledge and the incidence of anemia in adolescent girls (p = 0.870), and there was no relationship between nutritional status and the incidence of anemia in adolescent girls in Kupang (p = 0.058). Keywords: Anemia, Nutritional Knowledge, and Nutritional Status